THE IMPLEMENTATION OF INDEPENDENT READING ON MINI STORIES IN TEACHING WRITING NARRATIVE TEXT IN SENIOR HIGH SCHOOL - PUTRI AISYIAH, AGITA (Retain: Journal of Research in English Language Teaching, 2014)
THE IMPLEMENTATION OF INDEPENDENT READING ON MINI STORIES IN TEACHING WRITING NARRATIVE TEXT IN SENIOR HIGH SCHOOL Agita Putri Aisyiah English Education Program, Faculty of Language and Arts, Surabaya State University Email: ag1t.ndutz@gmail.com Him’mawan Adi Nugroho, S.Pd., M.Pd. English Education Program, Faculty of Language and Arts, Surabaya State University Email: himmawan_95@yahoo.com Abstrak Sejak Bahasa Inggris menjadi Bahasa Internasional yang digunakan untuk berkomunikasi, pemerintah Indonesia memasukkan Bahasa Inggris menjadi mata pelajaran wajib yang harus dikuasai oleh siswa SMA. Oleh karena itu, siswa harus menguasai keterampilan dasar yang tidak hanya diucapkan tetapi juga ditulis sebagai teks meliputi mendengar, berbicara, membaca dan menulis. Dari keterampilan tersebut, menulis adalah salah satu keterampilan yang paling sulit karena siswa mengumpulkan informasi sebanyak mungkin sebagai sumber dan mengatur pikiran di atas kertas. Itulah mengapa menulis selalu menggabungkan membaca untuk mendapatkan ide-ide saat mulai menulis. Ide-ide itu sendiri didapat dari apa yang telah dibaca. Krashen di Bray (2003) menyatakan bahwa siswa yang membaca terus-menerus dapat memperoleh kemampuan menulis. Oleh karena itu dengan menggunakan Independent Reading pada cerita-cerita mini, siswa dapat berlatih menulis dan meningkatkan nilai tulisan mereka terutama yang berupa narasi. Djuharie (2008:41) menyatakan bahwa teks narasi adalah semacam cerita yang bertujuan untuk menghibur pembaca. Cerita tersebut dapat berupa cerita fiksi dan non - fiksi seperti cerita mini. Cerita-cerita mini itu sendiri berbicara tentang cerita rakyat. Dalam pengajaran menulis narasi dengan menggunakan strategi ini, guru memberikan enam langkah yang harus dilakukan oleh siswa setelah mereka menerapkan membaca independen. Ada tiga puluh lima siswa kelas XI di kelas XI - A5 di SMAN 22 Surabaya yang menjadi subjek dalam penelitian kualitatif ini yang menggambarkan pelaksanaan membaca independen cerita mini untuk mengajarkan keterampilan menulis teks naratif. Mereka dibagi menjadi tiga kategori; baik, cukup, dan buruk untuk mengetahui kemampuan siswa dalam menulis ulang. Data dari penelitian ini adalah dalam bentuk kata-kata, frase dan kalimat. Kemudian instrumen yang digunakan untuk mendapatkan data adalah lembar observasi dan penilaian menulis komposisi menggunakan rubrik. Berdasarkan hasil penelitian, guru meminta siswa untuk membaca cerita di luar kelas sebagai pekerjaan rumah. Kemudian, guru melakukan konferensi, mengulas pemahaman siswa tentang teks narasi, dan menulis ulang di kelas. Dalam melaksanakan membaca independen pada cerita mini, siswa antusias melakukan pembacaan independen di luar kelas, dan ditemukan bahwa sebagian besar dari mereka dikategorikan ke dalam tingkat yang baik dan ada beberapa dari mereka masih dikategorikan ke dalam tingkat rendah. Kemampuan menulis mereka masih dalam kriteria rata-rata. Hal ini ditunjukkan berdasarkan komposisi mereka yang telah dianalisis menggunakan ESL Komposisi Profil rubrik . Akhirnya siswa menikmati membaca cerita Mini di luar kelas, mendapat kesempatan untuk membaca banyak tentang teks naratif, membangun kebiasaan membaca, dan mengorganisir komposisi yang baik dengan menggunakan kata-kata sendiri setelah membaca cerita sebagai praktek menulis mereka. Disarankan kepada guru harus memilih cerita Mini yang menarik yang masih berkaitan dengan tujuan pembelajaran sebagai bahan bacaan, guru harus memberikan siswa komentar yang baik untuk mendorong mereka untuk membaca lebih lanjut dan menggabungkan strategi membaca dengan keterampilan lain selain menulis. Selain itu, disarankan bagi peneliti lain yang bisa dilakukan dalam tingkat yang berbeda dari mahasiswa dan dikombinasikan dengan teknik atau permainan lain atau kegiatan yang menarik. Kata Kunci: pengajaran keterampilan menulis, naratif, membaca independen, cerita mini Abstract Since English becomes an International language which is used to communicate, Indonesian government include English into a compulsory subjects which has to be mastered by senior high school students. Therefore the students have to master basic skills not only spoken but also written texts as listening, speaking, reading and writing. From those skills, writing is one of the most difficult skills because the writer gathers information as much as possible as sources and organizes the thought on their paper. That’s why writing always combines reading to get ideas to start writing. The ideas itself were got from what have already read. Krashen in Bray (2003) stated that the students who read continuously can gain in writing ability. Therefore by using Independent Reading on mini stories, the students can practice writing and increase their writing score especially narrative. Djuharie (2008:41) stated that narrative text is a kind of stories which purposes to entertain readers. It can be fictional and non-fictional story such as mini stories. The mini stories itself are talking about folktales. In teaching writing narrative using this strategy, the teacher gives six steps that should be done by the students after they implement independent reading. There are thirty-five eleventh grade students in XI-A5 class in SMAN 22 Surabaya were the subject in this qualitative research which described the implementation of Independent Reading on mini stories to teach writing narrative texts. They were divided into three categorized; good, fair, and poor to know the students’ ability in rewriting. The data of this study is in the form of words, phrases and sentences. Then the instruments used to gain the data are the observation checklist and rubric assessment of writing a composition. Based on the result, the teacher asked students to read stories outside the classroom as homework. Then, the teacher did conference, reviewed the students’ understanding about narrative text, and did rewriting in class. In implementing independent Reading on mini stories the students were enthusiastic doing independent reading outside the class, and it is found that most of them categorized into good level and there is a few of them still categorized into low level. The ability of their writing is still in average criteria. It is shown based on their composition which has been analysed using ESL Composition Profile rubric. Finally the students enjoyed reading mini stories outside the classroom, got an opportunity to read a lot about narrative texts, built reading habit, and organized a good composition by using their own words after reading stories as their practice writing. It suggests that the teacher should select the interesting mini stories which are still related to the learning objective as reading material, the teacher should give the students good comments to encourage them to read more and combine the reading strategy with other skill besides writing. In addition it is suggested for other researcher that it could be conducted in different level of students and combined with other technique or game or interesting activities. Keywords: teaching writing, narrative, independent reading, mini stories. INTRODUCTION Realizing the importance of English, Indonesian government involves English as compulsory subject that should be taught in formal schools from primary school to secondary school. As stated on 2006 English Competence Standard, the students must be able to understand and produce both spoken and written text. For the eleventh grade of senior high school students, they should master some texts which cover report, narrative, analytical exposition, spoof, and hortatory exposition. Those are the genre of the text which is required to be mastered by them in the end of learning process. Moreover, there are four skills that should be mastered by students. One of them is writing. Writing is very needed to be mastered by the students since it can affect other skills. Writing can be a great tool to help students to learn how to form language, how to spell, how to put together a plot, and how to make a logical argument. Hence, writing is needed to be mastered by the students. Unfortunately, writing is one of the skills that most students are not interested in. It is the most complex skill since every single error is counted and it cannot be easily produced. Bell and Burnaby in Nunan (1991:6) said that: “Writing is an extremely complex cognitive activity that inquires the writer to demonstrate control of several variables at once. At sentences level, they include control of contents, format, sentence structure, vocabulary, pronunciation, spelling and letter formation. Beyond the sentence, the writer must be able to structure and integrate information into cohesive and coherent paragraphs and texts”. Teaching learning writing is not easy to do. Dhiasa (2009) stated that the students often face difficulties in learning writing. They are difficult to show their imagination. They spend much time to get the ideas to start writing. They do not have enthusiasm to write. Moreover, they have a few of literary review. These are caused by many reasons such as poor knowledge, and lack of time to practice writing. Finally, they cannot write creatively and well then they get bad score and nasty comments. Hadaway et al. in Diaz-Rico (2004:166) declared that writing can make us reach beyond ourselves. It is truly the most complex of the communication arts that combines reading and oral language. It is meant that writing is not a single activity. It is not only about writing but also about reading. Reading is completely important to start to write. It is impossible to write without having any ideas. The ideas itself can be taken from what have already been read. Reading and writing are connected each other. A new idea might appear after finishing reading, and writing is the patch to put that new idea. It means that they are inseparable activities. Krashen in Kusumawardhani (2006:2) stated that reading can help the students become a good reader, get an adequate vocabulary, master grammar, become a good speller and develop a good writing style. Reviewing the problem mentioned above, it is needed many kinds of methods, techniques or strategies to teach writing. There is a strategy to learn writing which is integrated with reading. It is called Independent Reading. Krashen (1993) in (Bray, 2002) provides an overview of research indicating that learners who read continuously can gain in reading comprehension, vocabulary development, and writing ability. Moreover, Elbow and Belanoff (2000) cited in Day (2004) stated that there is an activity which involves students in free writing. However, they are not asked to rewrite any topic they want; they are asked about what have been read, especially on mini stories. It allows the students a set period of time to think about their texts before they begin to rewrite. Therefore, Independent Reading on mini stories is seen to be the effective way in getting the students’ knowledge as literary review about activities in the past before they start writing something. This strategy is applied in Senior High School which is integrated with one genre of texts that eleventh graders have to be mastered. It is a narrative text. Narrative text is a text that tells a story in the past. By mastering this text, the students are expected to be able to express their feeling, thought and ideas about the past activities after they read the mini stories. RESEARCH METHOD This research is design based on descriptive qualitative research. It described the implementation of Independent reading on mini stories in the teaching writing narrative text in senior high school. Charter (1972:78) in Rifa’i (2007) said that descriptive qualitative studies include current condition which concerns the nature group of person, a group of objects, a class, etc. and it involves of inductive, analysis, classification, or measurement. It is meant that the purpose of this study is to describe an event that happens in the society and does not examine any hypothesis. The subject of the study was the English teacher and the students of eleventh graders, XI-A5 class in SMA Negeri 22 Surabaya. This class was chosen because narrative was taught in the eleventh graders. The teacher is also implemented Independent Reading on mini stories to teach writing narrative to the eleventh graders in three meetings. The data of this study are in form of information which is taken by observing the real situation when the teaching and learning happened in the class and collecting the students’ rewriting tasks in form of composition after being taught using Independent Reading. Then, the researcher classified the students’ rewriting in form of composition based on its organization, content, vocabulary, language use and mechanic using ESL Composition Profile. There are two instruments are used in getting the data. They are observation checklist in the form of “yes” or “no” option and students’ task to investigate the students’ writing ability after being taught by using of Independent Reading on mini-stories. The data for this study are taken by observing the real situation when the teaching and learning happened in the class and collecting the students’ rewriting tasks in form of composition after being taught using Independent Reading strategy. The topic was about folklore. Then, the researcher would classify the students’ rewriting in form of composition based on its organization, content, vocabulary, language use and mechanic using ESL Composition Profile. This method made the researcher easier to classify and identify the elements of writing that used by the students in their narrative text writing composition. This study was analysed descriptively. There are several steps to analyse the data. The observation checklist was used to check the observed aspect by checking “yes” or “no” in the real activities which happened in the classroom when the teacher applied Independent Reading on mini stories in each step during teaching writing narrative text. The result of observation was described, presented and analysed related to the facts that happened in the class. Then, the students’ task in form of composition which has been analysed by using ESL Composition Profile was divided into three groups, good, fair, and poor. It was used to describe the students’ writing result after being taught by using Independent Reading strategy on mini stories. Finally all of the data was combined to make a conclusion and suggestion. FINDINGS AND DISCUSSIONS Findings The researcher used the data from observation checklist. It was limited to the material, the strategy, and the teaching learning process. Moreover, the researcher used the data from the students’ task in form of composition which were collected in three meetings. They were presented through description. Then, the data were analysed and categorized into three different levels; good, fair, and poor. The Implementation of Independent Reading on Mini Stories in Writing The first observation was done on Tuesday, 4th February 2014 in XI IPA 5 class. In this meeting, the teacher introduced the Independent Reading strategy and reviewed narrative text. The students should read a mini story then rewrite it by using their own words. The teacher gave folklore story because it was familiar with the students. The folklore story was given in order to make the students read easily and happily. It is given because the folklore was based on the learning objectives. In pre-activity, the teacher greeted and checked the students’ attendance list. Unfortunately, three students were absent. Then, the teacher reviewed a little bit about simple past tense and narrative text which has been taught last semester. The explanation covered the function, the generic structure and the language features of the text. Mostly, the students still remember the elements of narrative text which is shown that they could answer the teacher’s questions about it. Moreover, they could analyse the generic structure of narrative text. In introducing the strategy which would be done, the teacher started to discuss about the books or texts that the students have read in their whole life. He also asked the students’ feeling after they read. Surprisingly, most students like reading books but they did not read any books or texts in English. They prefer reading in Bahasa Indonesia to English. After that, he asked the benefit of their reading activity. Most students answered that they felt very happy and gave respond enthusiastically. In whilst-activity, the teacher gave the first story about Aji Saka as the reading material to the students. The story is from their English book. This story has already given in the last semester. It is chosen because the students have already comprehended the story very well to make the students feel free to read and rewrite easily. It is the way the teacher used to introduce the strategy which integrated with writing. The students were asked to read the text in the classroom. This text was the easiest and the shortest one which was aimed to make the students enjoy reading. After the students finished reading the story, the teacher asked the students to collect the story in front of class and prepared a piece of paper. Then, he started to do the writing activity. The teacher gave instruction step by step to the students to start rewriting the story they have just read. In post-activity, the teacher asked students to collect their rewriting task. Before the teacher closed the meeting, the teacher gave new stories as the second material. The students should read them at home as homework. Then, the teacher reviewed some tips on enjoying reading. In summary, in the first meeting, the researcher found that the students were lazy and bored to read the story although the story was familiar. It is because the lesson was started after the break time. It was not only that, but there also was no van which made the class hot, so the students could not read with pleasure. Moreover, the students were not sure about the instruction of writing. It is showed when the teacher gave instruction step by step; some students seemed to not understand well what they had to do. They were so confused. It is because the teacher gave the instruction in English too fast. Seeing the students did not know what they had to do, the teacher combined the language he used with Bahasa Indonesia and English slowly. He also analysed the task in order to know the students’ shortcoming in rewriting a story in form of composition. It is hoped that the students could realize their mistakes and did not repeat the same mistakes for the next writing tasks. The second observation was conducted on Friday, 7th February 2014. The teacher has already analysed the students’ task in rewriting narrative text on the previous meeting, so that, the teacher knew the initial ability of the students. In this meeting the teacher would ask the students to rewrite one of the stories about Jaka Tarub and Nawang Wulan or The King, The Young Poor Fisherman, and The Fish which have already been given on the previous meeting as their homework by using the same instruction. Just like in the first observation, the teacher did the same activities in the class. In addition, in this meeting the teacher asked the students’ obstacles during reading, the differences between reading inside and outside the classroom and also the students’ feeling after reading. Most students gave their respond after they read the stories. The obstacles that the students had were varied such as they felt sleepy during the reading and they were not interested in the material because there were not enough pictures that made them enjoy reading. However, the students felt better when they read the stories outside the classroom. It is because they did not need to read in rush so they had much time to finish their reading. Therefore they could understand the story well. Then, the students also gave their respond about their feeling after reading. Most of them were excited to read more and more. They enjoyed reading because the material that they read were understandable and the words in the story were very common. After that, the teacher reviewed the previous story for a while in order to correct the students’ mistakes that they made in rewriting the story on the previous meeting. Therefore, the teacher knew the students’ ability in writing. In summary, in the second meeting, the teacher found that the students have enjoyed reading outside the class and understood what they had to do in writing activity. Therefore teacher used English in giving the instruction of rewriting. It is not only that, the teacher also gave music to make the students relax. They seemed to be more confident on their ability to remind, rethink and rewrite the story than previous meeting. Then the third observation was conducted on Tuesday, 11th February 2014. It was conducted in the same class. In this meeting, the teacher asked the students to rewrite one of the stories they have already read about The Gift of Jackal, The Wicked Magician or Love Conquers Death as reading material. All the process of this meeting was the same as the second meeting. The Students’ Narrative Text Result after the Implementation of Independent Reading On Mini Stories in Teaching Writing Narrative Text In this part, it deals with the students’ narrative writing result after the implementation of independent reading on mini stories in teaching writing narrative text from the first, the second and the third task. The students’ narrative writing were analysed by using ESL Composition Profile; that are organization, content, vocabulary, language use, and mechanic. Afterwards, they were divided into three levels. They are good, fair and poor. The result can be showed in the table below, Level Number of the students First task Second task Third task Very Good - - - Good 6 9 13 Fair 8 10 12 Poor 18 16 10 Table 4.1 The Result of Students’ Narrative Writing in the first, the second and the third task. In the first task, the teacher used the story about Aji Saka to rewrite. It is because the story was the easiest and the shortest. There are five aspects which have to be analysed in rewriting narrative story in form of composition. The content is the first and the most important aspect. It tells the ideas of the writer which they wanted to write. The second aspect is organization. In this part of writing narrative text, the students should write the story based on the generic structure of narrative. It deals with orientation, complication and resolution. Then, the third aspect in writing narrative text is vocabulary. It is about the words choice and usage of the writer which they want to share. The students applied the vocabulary they have learned while doing independent reading on mini stories to make their own words more different than the original. The next important aspect is language use. This aspect deals with the students’ ability in language which include with sentence construction, tenses, word order or function, pronoun, and preposition. The last aspect in writing narrative text is mechanic. The term mechanics deals with convention, spelling, punctuation, capitalization, and paragraphing. Based on the first task in the first meeting, it can be concluded that there were many students who were still confused to develop the ideas, composing the generic structure of the narrative text, making good sentences by using sophisticated range of vocabulary, creating good construction, and also demonstrating mastery of convention. Meanwhile in the second task, it is stated that some students showed a few good changes in writing narrative text. They occasionally made errors in delivering ideas, composing generic structure and mastering convention. However, in choosing the vocabulary and using the correct tenses, the students still got difficulties to practice it into a good story. It is because most students considered that the tenses were too difficult to be understood, and also it is because the teacher usually conducts the test for only the tenses. The teacher used Jaka Tarub and Nawang Wulan and The King, The Young Fisherman and the Fish as the second mini stories as reading material. They are still about folklore. They are also longer than the first. It is because the students had some times to read them outside the class as their homework. The students could choose one of the stories above to rewrite into a good composition. In the third task, the students’ writing narrative result was better than in the first and second task. They could deliver the organization of the story, rarely made the same mistakes of using past tense, arrange the story in a good paragraph. The teacher used the stories about The Gifts of The Jackal, The Wicked Magician, and Love Conquers Death as reading materials. The collections of short stories were from Indian folktale. Moreover, those stories were covered in a book which titled as Love Conquers Death and other stories. Discussions From the data through observation checklist, it is obvious that the implementation of Independent Reading on mini story can be integrated with writing in teaching writing narrative text. It is shown that the students more enjoyed reading mini stories outside the class which can be seen from their conference with the teacher before starting to rewrite. It helped the students to build their interest in reading without any forces. It is in line with Harris (1998:3) stated that independent reading refers to the outside reading activity that students do on their own with no help or guidance from the teacher. In addition, it was normal if there were some students got difficulties in understanding the steps of rewriting the story during the teaching process. From this situation, the teacher switched the language to Bahasa Indonesia. By using bilingual which covers English and Bahasa Indonesia, the teacher could know the students’ comprehension in steps of rewriting a story. Thus, the students could rewrite the story using the steps of rewriting well. In the process of rewriting narrative text itself; it would need a lot of energy. It is because it had long process and need more times. Therefore, the teacher role was much needed. It is to help the students develop viable strategies for pre-writing (getting started, generating indefinite ideas, and collecting information), drafting (scrawling down the ideas, making rough draft), revising (checking rough draft, adding, deleting, modifying, and rearrange ideas), and editing (attending to vocabulary, sentence, structure, grammar and mechanic) (Gebhard, 1996). On the other side to answer the second statements of problem, which is ‘How is the students’ writing result after being taught by using of Independent Reading strategy on mini stories?’ The data was gathered from the students’ task of rewriting a mini story after being taught by using Independent Reading. The data was discussed from the first, second and the third observation in form of a composition narrative text. Based on the first students’ task, the students got difficulties to compose text based on the generic structure, to implement the past tenses in the story, and also to develop the ideas more detail. Few of them were confused in using the correct spelling, punctuation, paragraphing and capitalization and selecting the appropriate vocabulary. However, most students have shown changes in their narrative writing in the second and third tasks. It means that the students practiced writing well in term of content, organization, vocabulary, language feature and mechanic from the first task to the second task then the third task and they comprehended the elements of writing well. In the end, the students got better understanding in presenting their ideas to the development of narrative text, providing vocabulary better and richer, using their knowledge of English, implementing the convention rules in their narrative writing and achieved adequate result. It is in line with was stated by Krashen (1993) in Bray (2002) that reading continuously can help the students develop a good writing style. CONCLUSION AND SUGGESTION Conclusion It was concluded that by using Independent Reading on mini stories in writing activities, the eleventh graders of SMA Negeri 22 Surabaya have enjoyed reading mini stories outside the classroom, got an opportunity to read a lot about mini-story, built reading habit, reviewed grammar, and have organized a good composition by using their own words after reading stories as their practice writing. Moreover, in the process of doing this strategy, the teacher selected the material according to the criteria for standard competence of curriculum and based on the students’ level of difficulty in vocabulary, content and sentence construction. The teacher also gives a model and steps how to rewrite a short story. The last is about the process of writing itself. This is the time when the students were asked to rewrite the story they have already read at home to know the students’ result during the implementation of Independent Reading on mini stories in writing activities. The result is found that the students generally grouped as “GOOD” and few of them still grouped as “POOR”. It is because the students’ ability in that class is still in low level. However, this strategy could help students getting fluency in expressing their ideas in rewriting the story. It could be seen from their result that they rarely made mistakes in their rewriting. Suggestion Based on the conclusion above, it is important to give some suggestion to the teacher and other researcher. This suggestion is pointed to the teacher related to the implementation of independent reading on mini stories. First, the teacher should select the interesting mini stories which are still related to the learning objective as reading material. It is used to avoid the students’ boredom on reading folklore and to make students more enjoy on reading. Second, the teacher should give the students good comments to encourage them to read more and practice more in writing. Third, the teacher should find another ways to encourage students to practice writing regularly, so the ability of students on writing is getting better. In addition the suggestion is also pointed to the other researcher. It is suggested that it could be conducted in different level of students and combined with other technique or game or interesting activities REFERENCES Abbot, Gerry et al. (1981). The teaching of English as an International Language: A practical guide. London: William Collin Sons and Co. Ltd Agustien, Helena. I.R. (2004). The 2004 English curriculum in a Nutshell (paper): presented at national seminar the teaching of ESL in Indonesia; A Reflection. 2 October 2004. Malang. Universitas Negeri Malang. Badan Standar Nasional Pendidikan. (2006). Standard Kompetensi Lulusan Bahasa Inggris untuk Sekolah Menegah Atas dan Madrasah Aliyah. Jakarta: Depdiknas Bamford, J. &Day, R. R., Extensive Reading: What Is It? Why Bother? Retrieved from http://www.jalt-publications.org/tlt/files/97/may/extensive.html Bell, T. (1998). Extensive Reading: Why? and How? The Internet TESL Journal, IV(12). Bray, E. (2002). Using Task Journals with Independent Readers. Retrieved from www.americanenglish.state.gov on March 19th, 2013. Brown, H. Douglas. (2001). Teaching by Principle: An Interactive Approach To Language Pedagogy, Second Edition. New York: Longman: Inc. Bryne, Donn. (1991). Teaching Writing Skills. Hongkong: Longman Group Ltd. Cohen, L., Manion, L., & Morrison, K. (2005). Research Methods in Education. London and New York: Taylor & Francis Group. Day, R. R. (2004). Two Writing Activities for Extensive Reading. English Teaching Forum. Day, R. R. and Bamford, J. (2002). Top Ten Principles For Teaching Extensive Reading. (Online), (http://nflrc.hawaii.edu, diakses 19 Maret 2013). Depdiknas. (2004). Kurikulum 2004: Standar Kompetensi Mata Pelajaran Bahasa Inggris Sekolah Menengah Pertama Dan Madrasah Tsanawiyah. Jakarta Dhiasa, Indah Swandewi. (2007). The Implementation of “Response Journal” Strategy in Teaching Reading Narrative to the Eight Graders of SMP Negeri 5 Sidoarjo. S-1 Unpublished Thesis: UNESA Diaz-Rico, L.T. (2004). Teaching English Learner: Strategies and Methods. Boston. Pearson Education, Inc. Gebhard, Jerry Greer. (1996). Teaching English as a Foreign or Second Language. USA: The University of Michigan Press. Heaton, J.B. (1975). Writing English Language Test. London: Longman. Krashen, S. (1993). The power of reading: Insights from the research. Englewood, CO: Libraries Unlimited. Knoester, M. (2010). Independent Reading and the ‘Social Turn’: How Adolescent Reading Habits and Motivation Relate to Cultivating Social Relationships. Networks an Online Journal, 12(1). Kusumawardhani, Rahardian. (2010). The Implementation of Extensive Reading to the Tenth Grade Students of Senior High School. S-1 Unpublished Thesis: UNESA. Menrath, J. (2003), from http://www.menrath-online.de/documents/shortst1.pdf Nunan, David. (1991). Language Teaching Methodology: A textbook for teachers. Great Britain. Prentice Hall International Ltd. Oczkus, L. (2010). Super Practical Ways to Build an Independent Reading Program in Your Classroom: Guidelines and TOP 5 Independent Reading Strategies. Retrieved from http:// www.lorioczkus.com on February 28, 2013. O’Malley, J. M. & Chamot, A. U. (1990). Learning Strategies in Second Language Acquisition. Cambridge: Cambridge University Press. Oxford, R. L. (1990). Language learning strategies: What every teacher should know. New York: Newbury House/Harper & Row. Rahmawati, Yunyta Puji. (2009). The implementation of Extensive Reading in Senior High School. S-1 Unpublished Thesis: UNESA. Reid, Joy M. (1993). Teaching ESL Writing: Los Angeles. University of California. Rifa’i, A. (2007). Unpublished S-1 Thesis: the writing of analytical exposition text by the students who join English club activity in SMA Negeri 2 Nganjuk. Surabaya: UNESA Richards, J.C., Platt J. & Platt H. (1992). Longman Dictionary of Language Teaching and Applied Linguistics. Essex: Longman. Sim, Sangmin. (2007). Unpublished Thesis for achieving Doctor of Philosophy degree: A study on reading strategies in KSL class. Retrieved from http://unsworks.unsw.edu.au/vital/access/services/Download/unsworks:1136/SOURCE02?view=true on November 26th, 2013. Wenden, A. & J. Rubin. (1987). Learner Strategies in Language Learning. Englewood Cliffs, NJ: Prentice Hall.